ESTRATÉGIAS E DESAFIOS NA INCLUSÃO DO ESTUDANTE COM DISLEXIA NO SISTEMA PÚBLICO DE ENSINO: UMA REVISÃO INTEGRATIVA (REMUNOM, 2025)
The Dyslexia is a difficulty in the areas of reading, writing, and spelling, which can also be accompanied by other challenges, such as perception of dimensions. Therefore, school inclusion of children with dyslexia is essential so they have access to learning opportunities just like other students. The aim of this study was to investigate strategies and challenges in including students with dyslexia in the public education system. Specifically, it sought to review the concepts of dyslexia and how the school inclusion process occurs. The study was conducted using an integrative literature review method, utilizing articles indexed in the Virtual Health Library (VHL) and the Scientific Electronic Library Online (SciELO), published between 2016 and 2021. The keywords used to select the studies were: “Dyslexia,” “Public Education,” and “School Inclusion.” After the searches, nine (9) articles met the eligibility criteria. Of these, three (3) articles addressed the diagnosis of children with dyslexia, three (3) discussed the inclusion process, highlighting the relationship between family and school, and the remaining three (3) articles focused on the characteristics of dyslexia from a clinical perspective. As results, it was evident that the inclusion of students with dyslexia in the public education system occurs slowly, with limited resources for professionals, and does not fully align with legislation. This highlights the need for the government to develop targeted public policies and to promote further research on the topic. It is concluded that early diagnosis of dyslexia and collaborative efforts among education, health, and family are essential for effective interventions. Despite progress, Brazilian legislation still lacks specific norms to ensure the full inclusion of these students. Personalized pedagogical strategies and ongoing teacher training are fundamental for providing quality inclusive education.